Family matters the relationship of gender employment and other demographics to household consumption patterns - Evangelista, Mary Elynne M.; Sy, Matt Jemuel L.; Alburo, Florian A. (Quezon City School of Economics, University of the Philippines Diliman, 2021)
Throughout the years, the Philippines has struggled to lower its unemployment rate. Until 2019, the country saw a downward trend in unemployment, on the way to achieving its 3-5% unemployment rate goal in the Philippine Development Plan for 2017-2022. However, the COVID-19 pandemic in 2020 caused a global economic crisis, reversing the trend into new heights. The labor force participation rate in 2020 fell to its lowest in 15 years. Even more alarming is the staggering labor force participation gap between men and women, which hardly changed throughout the years. Inevitably, unemployment of household members affects the income of the household, which in turn affects consumption of different goods. This paper analyzes the impact of unemployment of household members, particularly of the husband and wife, on household expenditure on different types and categories of goods. Moreover, it assesses the impact of demographic factors on household consumption patterns using a subsample of labor force participants obtained from the 2015 merged Family Income and Expenditure Survey, and Labor Force Survey. (FIES-LFS) Using both a Tobit model and the Ordinary Least Squares (OLS) estimation method, we found that depending on the expenditure category, unemployment of the husband or the wife can either increase or decrease household consumption. Only the unemployment of the wife was found to have a significant negative effect on household food consumption, while only the unemployment of the husband has a significant negative effect on transport and communication expenditure. Demographic variables such as age, educational attainment, household size, and location were also found to have varying effects on consumption of different goods.
Thesis (BS Economics & BS Business Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Income -- Philippines; Expenditure -- Philippines; Unemployment -- Philippines